BILINGUAL INTERACTION IN EFL CLASSROOM - Sitti Rahmayanti; Muhammad Azwar Assiddiq; Sri Hariati Mustari; Abdulhalim Daud (Cakrawala Bahasa, 2020)
The objectives of the research were to find out (1) the way of the teacher to involve the students in bilingual interaction, (2) the EFL students’ attitude towards bilingual interaction, and (3) the impact of bilingual interaction on the students’ bilingual achievement. This research employed a case study design. The participants of this research consisted of 1 EFL teacher and 4 EFL students. The data were obtained through observation, interview, and document. The data were analyzed based on procedure of data analysis which consisted of data collection, data display, data condensation and conclusion: drawing/ verification. The findings showed that (1) there were three steps in teaching process by bilingual interaction, they were beginning the class, learning process, and closing the class. It also showed that teacher’s way are classified into a highly advocating teacher (HAT) who advocates use of bilingual interaction and endeavor to find an alternative ways to using L1/L2 during teaching; (2) there were two kinds of the EFL student’s attitude toward bilingual interaction. Those were positive attitude and negative attitude. It also showed that there were some categories that EFL students’ attitude toward bilingual interaction in EFL classroom. They were highly interesting student (HIS) where student feeling that cause special attention to some object and readiness to learn about something, highly monitoring teacher (HMT) where the teacher monitors her instructional language to attract students’ attention in learning English based on their condition, and highly responding student (HRS) where student respond the explanation of material from teacher seriously; and (3) there were two of students’ bilingual achievement, those are high achievement and low achievement. So, it is showed that bilingual interaction give impact on the student’s achievement especially of students’ bilingual achievement. It also showed that there were some categories that EFL students’ attitude toward bilingual interaction in EFL classroom. They were highly monitoring teacher (HMT) where the teacher monitors her instructional language to attract students’ attention in learning English based on their condition and highly responding student (HRS) where student respond the explanation of material from teacher seriously. The findings led to the conclusion that bilingual interaction made the teacher- students and student- students more interactive within the classroom. In addition, the students were even confident to speak and influenced their attitude so they were actively participating in classroom activities and felt comfort interacting to the class by using bilingual interaction. Moreover, a teacher’s expectation shaped a teacher’s behavior, attempting to teach more and create a more positive atmosphere that led them to higher achievement.